Regulating internet access in UK public libraries: legal compliance and ethical dilemmas. Issue 1 (14th March 2016) - Muir, Adrienne; Spacey, Rachel; Cooke, Louise; Creaser, Claire
Abstract : Purpose: – This paper aims to consider selected results from the Arts and Humanities Research Council (AHRC)-funded "Managing Access to the internet in Public Libraries" (MAIPLE) project, from 2012-2014. MAIPLE has explored the ways in which public library services manage use of the internet connections that they provide for the public. This included the how public library services balance their legal obligations and the needs of their communities in a public space and the ethical dilemmas that arise. Design/methodology/approach: – The researchers used a mixed-method approach involving a review of the literature, legal analysis, a questionnaire survey and case studies in five public library authorities. Findings: – UK public library services use a range of methods to regulate internet access. The research also confirms previous findings that filtering software is an ubiquitous tool for controlling access to and protecting library users from "inappropriate", illegal and harmful internet content. There is a general, if sometimes reluctant, acceptance of filtering software as a practical tool by library staff, which seems to contrast with professional codes of ethics and attitudes in other countries. The research indicates that public library internet access will be a valued service for some time to come, but that some aspects of how public library services regulate internet access is currently managed can have socially undesirable consequences, including blocking legitimate sites and preventing users from accessing government services. Education could play a greater part in helping the general population to exercise judgement in selection of materials to view and use. This does not preclude implementing stricter controls to protect children, whilst allowing public libraries to continue providing a social good to those who are unable to otherwise participate in the digital age. Research limitations/implications: – The response to the survey was 39 per cent meaning that findings may not apply across the whole of the UK. The findings of this study are compared with and supplemented by other quantitative sources, but a strength of this study is the depth of understanding afforded by the use of case studies. Originality/value: – This paper provides both a quantitative and qualitative analysis of how internet access is managed in UK public libraries, including how library services fulfil their legal obligations and the ethical implications of how they balance their role in facilitating access to information with their perceived role as a safe and trusted environment for all members of their communities. The findings add to the international discussion on this issue and stimulate debate and policy making in the UK.